An assessment of oil palm waste products as fertilizer and growth media / Siti Fatihah Osman - Osman, Siti Fatihah (Faculty of Plantation and Agrotechnology, 2015)
The rapid expension of oil palm plantation and production in Malaysia contribute in large quantities of wastes being discharged. Direct discharged of the wastes may cause some environmental problem if not treated carefully. Thus, this study was conducted to assess the oil palm wastes as fertilizer and growth media. Three types of compost were dried compost, aerobic compost and anaerobic compost. All these three compost were composted from EFB, POME and OPDC. The result showed that utilization of wastes as growth media and fertilizer has been significant effect toward the plant growth. Addition of growth media from wastes to cocopeat has proven to be effective in improving vegetative growth of rockmelon. But, different types of compost do not contribute to significant effect toward plant growth performance.